Practical implementation of inclusive preschool education in Ukraine - Kalinina, Tetiana; Karnaukhova, Antonina; Mashovets, Marina; Shvaliuk, Tetiana; Telna, Olha (My University, 2022)
The right of children with special needs to education is realised through the introduction of inclusive education. Such practice is common in many countries around the world. An inclusive setting in early childhood education protects children from segregation and negative attitudes from others. In Ukraine, in connection with European integration, preschool inclusive education is actively developing. Accordingly, studying of inclusive education and the practice of preschool educational institutions for children with special educational needs in the country is relevant, and determining the specifics of this process became the purpose of this study. Analysis of the legal framework, method of comparative analysis, synthesis and analysis of quantitative indicators, questionnaires, systematisation and generalisation of statistical data were used during the research. A comparison of inclusive preschool education implementation experience in the European Union (EU) and Ukraine was conducted and the main trends in the development and implementation of inclusive education in Ukraine were identified. It was found that membership in the EU has a positive effect on both pre-primary education in the member states and the practice of inclusive education. This study can be useful for educators and policy makers in Ukraine for developing ways to improve the et al. situation with inclusive education both in preschool educational institutions and in schools, as well as for educators and policy makers from other countries, especially the Commonwealth of Independent States (CIS) countries, where similar processes are taking place in their educational systems.
Practical implementation of inclusive preschool education in Ukraine / T. S. Kalinina, A. V. Karnaukhova, M. A. Mashovets T. M. Shvaliuk, O. A. Telna // Review of Education, 2022. – Vol. 10. – Issue 1 April. – Р. 1–17.
Keywords: практичні аспекти, вихованці дошкільного віку, захист прав, особливі освітні потреби, спеціальні знання та вміння; practical aspects, preschool pupils, protection of rights, special educational needs, special knowledge and s